2020
DOI: 10.1111/eea.12943
|View full text |Cite
|
Sign up to set email alerts
|

Intraguild predation and cannibalism among Dicyphini: Dicyphus cerastii vs. two commercialized species

Abstract: Dicyphine mirids are one of the most important groups of predators on tomato. In the Mediterranean region, several species in the genera Dicyphus, Macrolophus, and Nesidiocoris (Hemiptera: Miridae, Bryocorinae, Dicyphini) colonize protected horticultural crops. In Portugal, Nesidiocoris tenuis (Reuter) is increasingly abundant in the mirid species complex of tomato crops and appears to be displacing the native Dicyphus cerastii Wagner. In order to know whether intraguild predation (IGP) can explain the decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Therefore, an insight into predator preferences may help to understand and predict the efficacy of D. cerastii in multiple prey situations. Dicyphines can also present cannibalistic and intraguild predatory interactions [87,88]. Both these direct, and indirect interactions such as competitive displacement [31], may also affect the success of biological control programs with these predators.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an insight into predator preferences may help to understand and predict the efficacy of D. cerastii in multiple prey situations. Dicyphines can also present cannibalistic and intraguild predatory interactions [87,88]. Both these direct, and indirect interactions such as competitive displacement [31], may also affect the success of biological control programs with these predators.…”
Section: Discussionmentioning
confidence: 99%
“…Many Hemiptera insects are known for their cannibalistic behavior, such as Arizona backswimmers Frank (Zalom, 1978), Triatoma infestans Klug and Triatoma sordida Stal (Ryckman, 1951), Arctocorisa carinata and Callicorixa producta (Pajunen and Pajunen, 1991), Xylocoris flavipes Reuter (Richard, 1979), Notonecta hoffmanni (Orr et al, 1990), Dicyphus cerastii Wagner, and Macrolophus pygmaeus Ranmbur (Goncalo et al, 2020) which would prey on its immature offspring. Our previous research showed that female A. custos were more active predators (ate more eggs than males) (Wu et al, 2020), while males did not participate in egg cannibalism.…”
Section: Introductionmentioning
confidence: 99%
“…Aspects of predator behavior are addressed by Duarte et al (2021) who report on intraguild predation (IGP) and cannibalism within Dicyphini (Hemiptera: Miridae). Predaceous mirids are common in horticultural crops and some species are also released for biological control, which might displace naturally occurring species.…”
mentioning
confidence: 99%